Assessment of heavy metal contamination in the surface sediments: A reexamination into the offshore environment in China. Issue 1 (15th December 2016) - Chen, Hongzhe; Wang, Jigang; Chen, Jinmin; Lin, Hui; Lin, Cai
Abstract: The contents of Cu, Pb, Zn, Cd, Cr, Hg and As in the surface sediments of over 668 sites were monitored in a comprehensive program for assessing the degree of heavy-metal pollution and adverse biological effects of the offshore sediments in China. The contamination factor and geoaccumulation index indicated that As and Pb might be two of the most influential pollution loading in these metals. Cluster analysis separated 19 areas in China's near seas into 7 groups with different pollution characteristic, where the sediments along Zhejiang coast were the most highly-contaminated. Based on biological adverse effects index and sediment quality guideline for As, nearly half of sites in China's near seas induced slight adverse biological effects. With correlation analysis, self-organizing map and factor analysis, different sources as well as various adsorption mechanisms/anthropogenic factors were suggested to be important roles in altering the concentration of heavy metals in the sediments. Highlights: Based on SQGs for As, nearly half of sites induced slight biological adverse effects. Several anthropogenic contributions to the pollution loading could be concluded. Sediments in Zhejiang, Guangdong and Bohai Gulf coast were proven most polluted. The most contaminated areas were adjacent to great river estuaries.